Online ludic activities and their effectiveness in english language learning at Medalla Milagrosa Elementary School 2016 - Espinosa Cubilla, Anthony Davis (UDELAS, 2016)
This research has a main goal; to offer some new advantages through the use of online ludic activities in order to develop the new student generation learning process; it will identify how students can learn english through different online activities, and the different current devices according with the technological landscape. Moreover, it provides to the teachers a gyude ti facukutate the second language acquisition to the digital natives or z generation, these new technological tools will make the learning process understandable and easier for these new students generations.